REINTEGRASI SAINS DAN ISLAM BAGI PRAKTISI PENDIDIKAN (SUATU TINJAUAN EPISTIMOLOGI DAN AKSIOLOGI) - Usman Usman (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2010)
Science and Islam are basically one, under the domain of wahidat al-Wujud. Within the domain, knowledge (science) has same unity and value to the knowledge of Allah. However, as it reached the earth, multi-fragmentation took place due to different capacity of human brain where generically it has different shape and limitation. One brain compared to the other one has its own portion which is called individualistic differentiation. Such individualistic differentiation is the realization of differences, limitations, and perspectives which are different from one another and similarity as well.